2019
DOI: 10.1063/1.5082220
|View full text |Cite
|
Sign up to set email alerts
|

Resistive detection of the Néel temperature of Cr2O3 thin films

Abstract: Although bulk magnetic properties of various antiferromagnets have been vigorously studied since long ago, their properties in the form of thin films, which are more relevant to antiferromagnetic spintronic devices, have not been investigated as much. In this work, we characterized the N eel temperature of Cr 2 O 3 thin films by investigating the temperature dependence of the spin Hall magnetoresistance in Cr 2 O 3 /Pt bilayers. A precise determination of the N eel temperature was made possible by carefully de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…5,6 The Pt/Cr 2 O 3 system has received growing attention lately since it was found to be a promising material for both catalytic and magnetic property investigations. [30][31][32][33][34][35] Kasikov et al 30 performed the deposition of Pt islands on Cr 2 O 3 followed by exposure to H 2 and CO diluted in synthetic air and heating at 723 K. The XPS spectra confirmed significant Pt 2+ and Pt 4+ chemical state contributions. After heating at 673 K in an ultra-high vacuum (UHV), an almost complete reduction of the platinum atoms to Pt 0 was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The Pt/Cr 2 O 3 system has received growing attention lately since it was found to be a promising material for both catalytic and magnetic property investigations. [30][31][32][33][34][35] Kasikov et al 30 performed the deposition of Pt islands on Cr 2 O 3 followed by exposure to H 2 and CO diluted in synthetic air and heating at 723 K. The XPS spectra confirmed significant Pt 2+ and Pt 4+ chemical state contributions. After heating at 673 K in an ultra-high vacuum (UHV), an almost complete reduction of the platinum atoms to Pt 0 was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…If an antiferromagnetic transition occurs in the layer beneath the Pt layer, distinct SMR responses of R 1 and R 2 below and above T N result in an inflection in ΔR (refs. 22,36,37 ). In fact, the value of ΔR for both the thick-MnTiO 3 monolayer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, with experimental methods applied to bulk crystals 10,[13][14][15] , it is difficult to evaluate magnetism in ultrathin films, particularly for cases of antiferromagnetism and quantum spin liquids. Thus, we studied the surface magnetic order using the spin Hall magnetoresistance (SMR) method, which enables electrical characterization of ferromagnetic 32 and antiferromagnetic transitions [33][34][35] , and magnetic anisotropy. By measuring SMR arising at the interface of Pt and MnTiO3 ultrathin films, we have recently demonstrated that the bulk Néel temperature TN (~ 63 K) 36 and the uniaxial magnetic anisotropy along the c-axis direction persist down to the film thickness of 2.9 nm ~ 2 u.c.…”
Section: Investigation Of Surface Magnetic Order By Spin Hall Magneto...mentioning
confidence: 99%
See 1 more Smart Citation
“…Below 280 K (~Néel temperature of Cr2O3 thin film 20) ), the coercivity of the Pt/Co/Au/Cr2O3/Pt films seemed to be enhanced compared with the reference sample, and this enhancement was observed for the film with tCr2O3 = 5.7 nm.…”
Section: A D V a N C E P U B L I C A T I O Nmentioning
confidence: 97%